2020
DOI: 10.1021/acsenergylett.0c01895
|View full text |Cite
|
Sign up to set email alerts
|

Mechanocatalytic Ammonia Synthesis over TiN in Transient Microenvironments

Abstract: Environmentally friendly and energy-efficient ways to produce ammonia are essential to meet global food demands. Here, a new approach for ammonia production at nominally ambient conditions is introduced. As proof of concept, ammonia is synthesized mechanocatalytically by ball milling titanium in a continuous gas flow. The ammonia synthesis reaction is proposed to follow a transient Mars− van Krevelen mechanism under mechanically activated conditions, where molecular nitrogen incorporation into the titanium lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 57 publications
1
51
0
Order By: Relevance
“…To finally prove that ammonia formation results from activation of nitrogen and not impurities (e.g. dissolved N in the stainless steel), two control experiments were performed: A batch reaction using 15 N 2 produced exclusively 15 NH 3 (see Table S3, entry 64 and Figure S25) and a continuous-flow experiment under exclusion of nitrogen gas resulted only in insignificant values of 10 ppm of ammonia (see Table S5, entry 81 and Figure S26). Significant amounts of ammonia in this experiment could only be produced after again dosing nitrogen gas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To finally prove that ammonia formation results from activation of nitrogen and not impurities (e.g. dissolved N in the stainless steel), two control experiments were performed: A batch reaction using 15 N 2 produced exclusively 15 NH 3 (see Table S3, entry 64 and Figure S25) and a continuous-flow experiment under exclusion of nitrogen gas resulted only in insignificant values of 10 ppm of ammonia (see Table S5, entry 81 and Figure S26). Significant amounts of ammonia in this experiment could only be produced after again dosing nitrogen gas.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, Tricker et al claimed a mechanocatalytic synthesis of ammonia over TiN in a common laboratory shaker mill. [15] However, during milling no ammonia was observed in the gas phase, and ammonia was determined by washing the milled solid with an aqueous solution, so that hydrolytic ammonia formation from a nitride seems possible, even probable. A true step towards mechanochemical ammonia formation was taken recently in a chemical looping process.…”
mentioning
confidence: 99%
“…16 These harsh operation conditions make the Haber-Bosch process a very energy-intensive process 17 (i.e. it consumes between 1% and 2% of the anthropogenic energy [18][19][20] ); and make the distributed ammonia production economically unfeasible, 21 restricting ammonia production to large centralized ammonia production facilities. 22 In addition to its large energy consumption, the current Haber-Bosch process is an important CO 2 source (i.e.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…26 Achieving this goal would make ammonia production more sustainable and economically profitable, enabling smaller local reactors, 27 and thereby distributed ammonia production networks in which ammonia would be directly generated at the consumption point. To present date, several promising strategies are being actively explored, including (mild conditions) thermochemical, [28][29][30] electrochemical, 31-34 photochemical, [35][36][37] photoelectrochemical, [38][39][40] plasma-activated, 41,42 and mechanocatalytical 21,43 ammonia production methods. So far, none of these methods has achieved acceptable ammonia yields and/or selectivities, and therefore the search continues as shown by the increasing number of works dealing with the Nitrogen Reduction Reaction (NRR).…”
Section: List Of Symbolsmentioning
confidence: 99%
“…The NH 3 is produced by the lattice N, leading to lattice vacancies which will be further replenished with the gaseous N 2 . [ 50,74,75 ] Moreover, the theoretical study of MN x for the NRR also suggested that transition metal nitrides, such as VN and ZrN, can suppress the HER and achieve the NRR at low onset potentials. [ 50 ]…”
Section: Fundamentals Of Electrochemical Nh3 Synthesismentioning
confidence: 99%